Timing and Management of Surgical Site Infections in Patients With Open Fracture Wounds: A Fluid Lavage of Open Wounds Cohort Secondary Analysis. Issue 3 (March 2021) - Prada, Carlos; Marcano-Fernández, Francesc A.; Schemitsch, Emil H.; Bzovsky, Sofia; Jeray, Kyle; Petrisor, Brad; Bhandari, Mohit; Sprague, Sheila
Abstract : Background: Many studies report on the incidence or prevalence of fracture-related surgical site infections (SSIs) after open fractures; however, few studies report on their timing and management outcomes. To address this gap, we used data from the Fluid Lavage of Open Wounds trial to determine timing of diagnosis, management, and resolution of SSIs. Methods: All participants included in this analysis had an SSI after an open fracture. Participants were assigned to a group based on the type of SSI as follows: (1) those who developed a superficial SSI and (2) those who had either a deep or organ/space SSI. Descriptive statistics characterized the type, timing, and management of each SSI. Results: Of the 2445 participants in the Fluid Lavage of Open Wounds trial, 325 (13.3%) had an SSI. Superficial SSIs were diagnosed significantly earlier [26.5 days, interquartile range (IQR) 12–48] than deep or organ/space SSIs (53 days, IQR 15–119). Of the 325 patients with SSIs, 174 required operative management and 151 were treated nonoperatively. For SSIs managed operatively, median time for infection resolution was 73 days (IQR 28–165), and on average, 1.73 surgeries (95% confidence interval 1.58–1.88) were needed during the 12 months follow-up. There were 24 cases whose SSIs were not resolved at the time of the final follow-up visit (12 months). Conclusions: Based on this study's findings and in contradistinction to the Centers for Disease Control and Prevention guidelines, after an open fracture, superficial SSIs were diagnosed at one month and deep/organ/space SSIs at 2 months. This information can allow for earlier infection detection. In addition, the knowledge that approximately 50% of the SSIs in our study required a reoperation and 3 months at a minimum to resolve will assist orthopaedic surgeons when counseling their patients. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.